A single infusion of ketamine improves depression scores in patients with anxious bipolar depression. (14th November 2014) - Ionescu, Dawn F; Luckenbaugh, David A; Niciu, Mark J; Richards, Erica M; Zarate, Carlos A
<x xml:space="preserve">Abstract</x> Objective Patents with anxious bipolar disorder have worse clinical outcomes and are harder to treat with traditional medication regimens compared to those with non‐anxious bipolar disorder. Ketamine has been shown to rapidly and robustly decrease symptoms of depression in depressed patients with bipolar disorder. We sought to determine whether baseline anxiety status reduced ketamine's ability to decrease symptoms of depression. Methods Thirty‐six patients with anxious (n = 21) and non‐anxious (n = 15) treatment‐resistant bipolar depression (types I and II; concurrently treated with either lithium or valproate) received a single infusion of ketamine (0.5 mg/kg) over 40 min. Post‐hoc analyses compared changes in the Montgomery–Åsberg Depression Rating Scale (MADRS) and Hamilton Depression Rating Scale (HDRS) in anxious versus non‐anxious depressed patients with bipolar disorder through 14 days post‐infusion. Anxious bipolar depression was defined as DSM‐IV bipolar depression plus a HDRS Anxiety/Somatization Factor score of ≥ 7. Results A linear mixed model revealed a significant effect of anxiety group on the MADRS (p = 0.04) and HDRS (p = 0.04). Significant drug effects (all p < 0.001) suggested that both anxious and non‐anxious groups had an antidepressant response to ketamine. The drug‐by‐anxiety interactions were not significant (all p > 0.28). Conclusions Both anxious and non‐anxious patients with bipolar depression had significant antidepressant responses to ketamine, although the anxious depressed group did not show a clear antidepressant response disadvantage over the non‐anxious group. Given that anxiety has been shown to be a predictor of poor treatment response in bipolar depression when traditional treatments are used, our findings suggest a need for further investigations into ketamine's novel role in the treatment of anxious bipolar depression.